Cost of care for persons with dementia: Using a discrete-time Markov chain approach with administrative and clinical data from the dementia service Centres in Austria - Alexander Braun; Paulina Kurzmann; Margit Höfler; Gottfried Haber; Stefanie Auer (Health Economics Review, 2020)
Background: There is growing evidence that the cost for dementia care will increase rapidly in the coming years. Therefore, the objective of this paper was to determine the economic impact of treating clients with dementia in outpatient Dementia Service Centres (DSCs) and simulate the cost progression with real clinical and cost data. Methods: To estimate the cost for dementia care, real administrative and clinical data from 1341 clients of the DSCs were used to approximate the total cost of non-pharmaceutical treatment and simulate the cost progression with a discrete-time Markov chain (DTMC) model. The economic simulation model takes severity and progression of dementia into account to display the cost development over a period of up to ten years. Results: Based on the administrative data, the total cost for treating these 1341 clients of the DSCs came to 67,294, 910 EUR in the first year. From these costs, 74% occurred as indirect costs. Within a five-year period, these costs will increase by 7.1-fold (16.2-fold over 10 years). Further, the DTMC shows that the greatest share of the cost increase derives from the sharp increase of people with severe dementia and that the cost of severe dementia prevails the cost in later periods. Conclusion: The DTMC model has shown that the cost increase of dementia care is mostly driven by the indirect cost and the increase of severity of dementia within any given year. The DTMC reveals also that the cost for mild dementia will decrease steadily over the time period of the simulation, whereas the cost for severe dementia increases sharply after running the simulation for 3 years.
Keywords: 330; Cost and cost analysis; Dementia; Discrete-time Markov chain; Administrative data; Cost simulation